Qualities of Diabetic Food Developed from Brown Rice and Oyster Mushroom - Sulistyowati, Etik; Kristianto, Yohanes; Handayani, Dian; Kusumastuty, Inggita; Videlia, Videlia; Kuncoro, Safiratuz Zahra ‘Aisy (Department of Nutrition, Faculty of Health Sciences, Universitas Brawijaya Malang, 2023)
The prevalence of diabetes mellitus has been increasing. This study aimed to develop Food for Special Dietary Use (FSDU) for individuals with diabetes. Different combinations of food ingredients were added to the basic formula, consisting of brown rice and mushroom flour in a ratio of 70% and 11%. The combinations used in the formulation were F1 = 9% moringa and fish flour, F2 = 10% carrot and fish flour, F3 = 11% moringa and tempeh flour, and F4 = 12% tempeh flour. The results showed that the FSDU contained energy, fat, and fiber ranging from 391.33–404.33 Kcal, 5.53–7.75 g, and 4.22–7.60 g per 100 g product, respectively. These values were slightly higher than the respective value of a commercial product. The panelists expressed positive acceptance of the developed FSDU products, with F2 chosen as the most preferred. The developed FSDU exhibited lower scores for feeling of hunger, desire to eat, and prospective food consumption compared to the commercial product. The product provided a feeling of fullness similar to the commercial counterpart. In conclusion, the FSDU based on brown rice and oyster mushroom with an additional 10% carrot fish flour would be the most preferred option for further use as FSDU for diabetics.